Particularly Interesting Cysteine- and Histidine-Rich Protein in Cardiac Development and Remodeling. (1st December 2009) - Liang, Xingqun; Sun, Yunfu; Chen, Ju
Abstract : Integrin-mediated cell-extracellular matrix interaction plays key roles in tissue morphogenesis and integrity. The Lin11-Isl-1-Mec-3 (LIM) domain-only particularly interesting cysteine- and histidine-rich (PINCH) protein functions as an adaptor essential for the assembly and function of the focal adhesion complex that links integrin signaling to the cytoskeleton and other intracellular signaling pathways and regulates diverse cellular processes such as cell adhesion, migration, growth, differentiation, and survival. Recent biochemical and genetic studies have greatly advanced our knowledge surrounding the molecular interactions and functions of each component of the focal adhesion complex and revealed a requirement for PINCH in early embryogenesis, in morphogenesis of the neural crest and cardiac outflow, and in myocardial growth and remodeling. In this review article, we will provide an overview of the current knowledge of the molecular interactions of PINCH with other components of focal adhesions, highlighting recent discoveries of the in vivo role of PINCH and discuss its potential implication for human heart disease.